Analisis Pengaruh PDRB Perkapita, Anggaran Sektor Kesehatan, Sektor Pendidikan Terhadap Indeks Pembangunan Manusia Se-Kabupaten Di Pulau Madura - Rizal Amrullah (Program Studi Ekonomi Pembangunan, 2022)
This study aims to determine the factors that influence the Human Development Index in the Madura Island region. This study uses a quantitative descriptive method and the variables used in this study are HDI, per capita GRDP, Health Sector Budget, and Education Sector Budget on Madura Island. The data used in this study were obtained from BPS East Java Province. The results of this study indicate that GRDP per capita has a positive effect, the Health Sector Budget has a negative effect, and the Education Sector Budget has a positive effect on the Human Development Index in all districts on Madura Island.